2012
DOI: 10.1007/s11010-012-1364-1
|View full text |Cite
|
Sign up to set email alerts
|

Geraniol modulates cell proliferation, apoptosis, inflammation, and angiogenesis during 7,12-dimethylbenz[a]anthracene-induced hamster buccal pouch carcinogenesis

Abstract: Oral carcinogenesis, a multistep process with multifaceted etiology, arises due to accumulation of heterogeneous genetic changes in the genes involved in the basic cellular functions including cell division, differentiation, and cell death. These genetic changes in the affected cell progressively increase the cell proliferation, angiogenesis, and inhibition of apoptosis. The present study investigated the modulating effect of geraniol on the expression pattern of cell proliferative (PCNA, cyclin D1, c-fos), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Ludwig et al [35] reported that mutant p53 gene and p53 protein expression has been reported in 30 to 50 % of mammary carcinogenesis. Detection of p53 protein by immunohistochemistry has become a routine method in pathology practice, and the presence of detectable p53 protein is an important prognostic marker that correlates with higher histopathologic grade, increased mitotic activity and aggressive behavior [63].…”
Section: Discussionmentioning
confidence: 99%
“…Ludwig et al [35] reported that mutant p53 gene and p53 protein expression has been reported in 30 to 50 % of mammary carcinogenesis. Detection of p53 protein by immunohistochemistry has become a routine method in pathology practice, and the presence of detectable p53 protein is an important prognostic marker that correlates with higher histopathologic grade, increased mitotic activity and aggressive behavior [63].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to compounds discussed, monoterpenes from turmeric may also account for its activities. The most common of these monoterpenes are ascaridol , borneol , carvacrol , carvone , cymene , geraniol , limonene , linalool , α‐pinene , terpinolene , and thymol . Among these monoterpenes, carvacrol, geraniol, and limonene have received considerable attention over the years.…”
Section: Anti‐inflammatory and Anticancer Activities Of Noncurcumin Cmentioning
confidence: 99%
“…The present study showed that treatment with geraniol significantly weakened the caspase-3 and caspase-9 activities in SCI rats. Similarly, Vinothkumar et al (32) reported that geraniol modulated the apoptosis and inflammation by decreasing the activities of caspase-3 and caspase-9. Thus, the findings of the present study suggested that the anti-apoptotic effect of geraniol has an essential protective role in SCI.…”
mentioning
confidence: 92%